Multiple signaling pathways in Sertoli cells: recent findings in spermatogenesis - Ni, Fei-Da; Hao, Shuang-Li; Yang, Wan-Xi (Cell death & disease, 2019)
The functions of Sertoli cells in spermatogenesis have attracted much more attention recently. Normal spermatogenesis depends on Sertoli cells, mainly due to their influence on nutrient supply, maintenance of cell junctions, and support for germ cells’ mitosis and meiosis. Accumulating evidence in the past decade has highlighted the dominant functions of the MAPK, AMPK, and TGF-β/Smad signaling pathways during spermatogenesis. Among these pathways, the MAPK signaling pathway regulates dynamics of tight junctions and adherens junctions, proliferation and meiosis of germ cells, proliferation and lactate production of Sertoli cells; the AMPK and the TGF-β/Smad signaling pathways both affect dynamics of tight junctions and adherens junctions, as well as the proliferation of Sertoli cells. The AMPK signaling pathway also regulates lactate supply. These signaling pathways combine to form a complex regulatory network for spermatogenesis. In testicular tumors or infertile patients, the activities of these signaling pathways in Sertoli cells are abnormal. Clarifying the mechanisms of signaling pathways in Sertoli cells on spermatogenesis provides new insights into the physiological functions of Sertoli cells in male reproduction, and also serves as a pre-requisite to identify potential therapeutic targets in abnormal spermatogenesis including testicular tumor and male infertility.